Afterimage and movement - Gyenes, Zsolt (ARTCADIA, 2025)
Color, space, sound, movement, and illusion go hand in hand, and this forms the basis of a holistic approach. Electronic-digital technologies allow different signals to be transformed into each other. Different media can complement each other organically, appearing inextricably together; like a melting pot, completely different things can take on a new form. This means, on the one hand, a return to „prehistory” and, on the other hand, the symbolization of the diversity of today’s „remix, remake culture”. All this is permeated by the realization that perception is saturated with characteristic, unique and wonderful functions.